2017
DOI: 10.1186/s12989-017-0211-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of copper oxide nanomaterials on differentiated and undifferentiated Caco-2 intestinal epithelial cells; assessment of cytotoxicity, barrier integrity, cytokine production and nanomaterial penetration

Abstract: BackgroundCopper oxide nanomaterials (CuO NMs) are exploited in a diverse array of products including antimicrobials, inks, cosmetics, textiles and food contact materials. There is therefore a need to assess the toxicity of CuO NMs to the gastrointestinal (GI) tract since exposure could occur via direct oral ingestion, mucocillary clearance (following inhalation) or hand to mouth contact.MethodsUndifferentiated Caco-2 intestinal cells were exposed to CuO NMs (10 nm) at concentrations ranging from 0.37 to 78.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 84 publications
(86 reference statements)
1
73
0
1
Order By: Relevance
“…IL8 leads to the recruitment of neutrophils to the site of damage and, therefore, implying that CuO nanomaterials lead to cellular damage in cells. In previous studies, the level of IL8 was found to increase twofolds when Caco 2 cells were treated with CuO NP . No significant effect on IL8 was observed in case of cerium oxide NP and the mixture of these NP.…”
Section: Discussionmentioning
confidence: 80%
“…IL8 leads to the recruitment of neutrophils to the site of damage and, therefore, implying that CuO nanomaterials lead to cellular damage in cells. In previous studies, the level of IL8 was found to increase twofolds when Caco 2 cells were treated with CuO NP . No significant effect on IL8 was observed in case of cerium oxide NP and the mixture of these NP.…”
Section: Discussionmentioning
confidence: 80%
“…[58,59] Apart from silver nanomaterials, CuO and ZnO nanomaterials also exhibited similar oxidative stress effects that induced cytotoxicity and damage to the ultrastructure of the intestine (Figure 5b). [60,61] Recently, Fe 2 O 3 NMs have been shown to disrupt the integ rity of intestinal barrier through affecting the expression of gammacatenin, Zona occludens1, and other integrity associated proteins in a sizedependent manner, in the order of 17 nm > 53 and 100 nm. [62] Consistent with this finding, another in vivo study has shown intestinal absorption of par ticles to be size dependent, with smaller particles (polystyrene microspheres and colloidal gold) being absorbed to a greater degree than larger ones.…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…For example, CuO NMs showed totally different behavior on the morphology of both differentiated and undifferentiated monolayer models of Caco2 cells (Figure 5c). [60] In spite of their adverse effects, NMs also show some benefits on designing test platform for nanotoxicity. .…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…5 CuO NPs are able to generate oxidative stress and significantly decrease cell viability in tumor cells. [16][17][18] Glioma is a type of brain and central nervous system tumors, which starts in supportive glial cells that surround nerve cells and help them function. 19 Cell division is a normal process to build new cells and tissues but it is stopped whenever there is no longer need for more cells or is a threat for the organisms to be destroyed by apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%